UCMSC-derived exosomal circDLGAP4 enhances HFF-1 cell proliferation and migration by promoting ZNF217 promoter H3K27 acetylation - Yun-lei Ma; Jia Fu; Yao-xue Zhang; Han-yue Xue; Yue-yue Luo; Wei-zhe Zhang; Shao-jia Kuang; Jia-qin Xu; Zun-Hong Liang (Molecular Genetics and Genomics, 2026)

Seasonal grazing drives complementary adaptive strategies in grasses and forbs via niche divergence: Evidence from a long-term experiment in alpine meadows - Peng Jiang; Hao-Zhe Zheng; Qing-Shan Fan; Lu-Ji Ade; Shu-Lin Wang; Fu-Jiang Hou (Agriculture, Ecosystems & Environment, 2026)

Numerical simulation of the effect of exhaust fan layout on indoor air quality in stacked-cage poultry buildings during winter - Yang Zixin; Fu Xueting; Liang Chao; Tu Yunan; Wang Chaoyuan; Wang Zhe (Computers and Electronics in Agriculture, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

O2 enhanced SF6 degradation in SiO2@TiO2 filled dielectric barrier discharge - Yalong Li; Zhe Huang; Kun Wan; Yangjing Le; Mingli Fu; Ying Zhang; Zhaodi Yang; Yan Luo; Xiaoxing Zhang (Journal of Environmental Chemical Engineering, 2026)

Pollution prediction of heating boiler plants based on data preprocessing and CNN-LSTM-attention model - Zhengda Lin; Jifeng Wang; Bingjie Yan; Zhe Fu; Liyan Liu; Dan Zhong; Xingwei Du; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

An integrated multiscale air quality modelling framework for industrial park pollution: Linking local emissions to regional transport - Tao Wang; Jie Li; Joshua S. Fu; Wei Wang; Bing Liu; Bin Zhao; Yibo Zhang; Jinxiu Pan; Feng Sun; Xiu’e Shen; Zhe Wang; Xiao Tang; et al. (Journal of Environmental Sciences, 2026)

Fusion of hyperspectral and multisource remote sensing data using intelligent optimized ensemble learning to estimate the SOC content of seven mangrove species in China - Jun Sun; Weiguo Jiang; Ziyan Ling; Peng Hou; Zhijie Xiao; Zhe Yang; Ze Zhang; Bolin Fu; Lu Liu; Yuyang Li; Xu He (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Biodegradable lead-free piezoelectric nanofibrous scaffold enables motion-activated meniscal tear repair - Xiaolong Yang; Xing Huang; Yulai Zhang; Yi Zhou; Zhe Xu; Yi Zhang; Laiming Jiang; Weili Fu; Jiagang Wu (Chemical Engineering Journal, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Numerical simulation of the evolution of the temperature field of phase change temperature-regulating asphalt pavement under the urban heat island effect - Dingjie Xu; Jiasheng Dai; Feng Ma; Zhen Fu; Chen Li; Yanzhe Zou; Yingjie Hou; Xiaolong Yang; Zhe Li; Meng Jia (Sustainable Cities and Society, 2026)

Iron-regulated crystallization in sensible-heat-driven glass-ceramics from molten lead-zinc smelting slag: Process-structure-property coupling and LCA quantification - Yibo Yang; Yusheng Tang; Hanguang Fu; Mengchen Xiao; Meichen Pan; Jixian Wu; Zhichuan Li; Zhe Tan; Zhixue Qu; Dean Pan; Xiaoguang Zhang (Process Safety and Environmental Protection, 2026)

High-capacity selective removal of Sb(III) by magnetic molecularly imprinted polymers in water: Mechanistic insights from experiments and DFT calculations - Kuiyuan Chen; Xiaodong Du; Xiongkai Zheng; Qixian Fu; Zhe Liu; Jingyang Li; Yingju Liu; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Ionic liquids and SWCNT synergistically construct a dual-transport network in PEDOT: PSS composite fibers for supercapacitor electrodes - Yuxin Fu; Xiuchen Wang; Gege Hang; Yanan Wang; Zhe Liu (Chemical Engineering Journal, 2026)

40Ar/39Ar geochronology, SrNd isotopes and melting conditions of the Dahongshan alkaline basalts: Constraints on mantle modification beneath the northern Yangtze Craton - Yue Song; Xuan-Ce Wang; Simon A. Wilde; Xiang-Zhong Li; Chong-Jin Pang; Si-Yu Hu; Yang Luo; Jia-Xu Tang; Si-Zhe Fu (Chemical Geology, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Retraction notice to “Influence of the morphological change in natural Asian dust during transport: A modeling study for a typical dust event over northern China” [Sci. Total Environ. 739 (2020) 139791] - Yu Tian; Zhe Wang; Xiaole Pan; Jie Li; Ting Yang; Dawei Wang; Xiaoyong Liu; Hang Liu; Yuting Zhang; Shandong Lei; Yele Sun; Pingqing Fu; et al. (Science of The Total Environment, 2026)

Numerical investigation of dynamic response of HDPE raft-cage aquaculture systems under combined wave-current conditions: Multi-System coupling analysis - Fei Fu; Xiaoying Zhang; Zhanbin Meng; Di Ren; Xiangxi Han; Jianxing Yu; Zhe Hu (Ocean Engineering, 2026)

Probabilistic building energy savings verification via triplet network-based adaptive reference day selection - Ziwei Xiao; Jing Zhang; Zhe Chen; Fu Xiao (Energy and Buildings, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

A coordinated scheduling approach with electricity peak shaving capability for integrated office Building-EV system - Jiesheng Yu; Yongming Zhang; Zhe Yan; Hai Ye; Weidong Fu; Hua Deng; Zhongyang Qian (Energy and Buildings, 2026)

Unveiling colloid-mediated mobilization of Cd/As/Cr by low-molecular-weight organic acids in high geological background soils - Qixian Fu; Zhe Liu; Lijuan Zeng; Zijuan Zhong; Jinfan Chen; Xiongkai Zheng; Han Ye; Xueqin Tao; Quan Chen; Bo Pan; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Resolving multi-metal encapsulation in coal gasification slag via an integrated activation and selective-separation strategy - Xiaoye Hong; Min Fu; Yanbing Gong; Qiqi Li; Zhe Sun; Yongfeng Zhang; Yinmin Zhang; Xiang He (Chemical Engineering Journal, 2026)

On-demand amorphous calcium phosphate-mediated regeneration of dentin and enamel using ion-regulated hydroxypropyl methylcellulose and carboxymethyl chitosan hydrogels - Zihan Cui; Zhiwen Liu; Zhixin Zhang; Danni Wang; Taoyu Chen; Baiping Fu; Ling Zhu; Long Zhao; Zhe Wang (Carbohydrate Polymers, 2026)

A multi-scale fracture prediction method based on improved deep embedded clustering - Yu-jia Lu; Chao Chen; Zhu-jiang Liu; Fu-bin Wei; Zhe-ge Liu (Applied Geophysics, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Decoding gibberellin–strigolactone interaction networks in cereal crops toward a next-generation Green Revolution - Jie Hu; Yunzhe Wu; Shuang Zhang; Qiaoling Zhang; Zhe Chai; Dan Li; Danlin Zhao; Binghui Wu; Xiuhua Gao; Xueying Liu; Kun Wu; Xiangdong Fu (Molecular Plant, 2026)

A framework approach for analyzing water transformation characteristics of typical watersheds in arid zones during irrigation periods - Jingming Liu; Jianli Ding; Jinjie Wang; Zhe Zhang; Jie Zou; Zipeng Zhang; Xiao Wang; Zan Fu; Xiangyu Ge (Environmental Modelling & Software, 2026)

Sustainable valorization of shield tunneling spoil via silane-coupled recycled mask fibers: Interfacial enhancement and engineering performance - Yu-Zhang Bi; Xin-Po Sun; Chun-Ying Wang; Tian-Xing Ma; Xian-Lei Fu; Zhe-Yuan Jiang (Sustainable Chemistry and Pharmacy, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Secondary metabolites from the endophytic fungus Hypoxylon sp. HK-37 derived from Aquilaria sinensis - Zheng-Zhuo Ren; Kai-Lei He; Fei Wu; Li Yang; Jing-Zhe Yuan; Ze-Sheng Li; Hao-Fu Dai; Wen-Jian Zuo; Hui-Qin Chen (Phytochemistry Letters, 2026)

Unveiling the mechanisms of mechanical stirring for enhanced performance and stability of algal-bacterial flocs treating low C/N synthetic wastewater - Jun-Jie Gu; Bin-Di Mao; Xiao-Xiao Dou; Bin-Xin Zhang; Jia-Wei Xu; Chun-Wan Fu; Bang-Jie Lan; Xin-Jie Zhang; Zhe Xu; Feng Gao (Bioresource Technology, 2026)

Anti-inflammatory diterpenoids from the wasp nest ( Nidus vespae ) of Vespula vulgaris against MSU-induced inflammation in Raw264.7 cells - Zhiling Yao; Tao Liu; Leyi Fu; Zitian Peng; Liju Zhang; Zhe Ren; Zhiping Wang; Xiaofei Zheng; Yifei Wang (Natural Product Research, 2026)

Enhanced SO2F2 degradation via Fe2O3-based catalyst coupled with DBD plasma - Yalong Li; Zhaodi Yang; Xiaoxing Zhang; Mingli Fu; Yangjing Le; Lei Yu; Huiyu Tan; Zhe Huang; Zhongfeng Wang (Journal of Cleaner Production, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Shionone ameliorates pulmonary fibrosis by activating mitophagy via PINK1-Parkin pathway - Yijia Su; Qiang Fu; Xilin Wu; Xianhua Che; Zhe Jiang; Xuezheng Li (Toxicology and Applied Pharmacology, 2026)

Analysis of cadmium sources in surface soil in typical karst regions: Anthropogenic input contribution and atmospheric transport impact - Zhe Liu; Guangyi Sun; Xian Wu; Weihai Yu; Heng Yao; Yu Lin; Chunlin Fu; Jinling Liu; Xinbin Feng (Journal of Hazardous Materials, 2026)

Optimizing dynamic thresholds with salt endmember constraints for lake mapping in arid regions - Zan Fu; Zhe Zhang; Jingming Liu; Qian Sun (Journal of Arid Environments, 2026)

The self-assembling amphibian-derived peptide (RADA)4-FZ1 pioneers a novel therapeutic platform for diabetic skin wound management - Zhe Fu; Jingyu Jiang; Qiuye Jia; Hao Zhu; Xinhe Shen; Yunjian Luo; Shaowei Chen; Tuanqing Li; Yutong Wu; Naixin Liu; Kun Guo; Ying Wang; et al. (Chemical Engineering Journal, 2026)

Phototransformation of benzodiazepines in water mediated by dissolved black carbon: Mechanisms and the structure-reactivity relationship - Zhi-Cheng Zhou; Bin Yang; He-Yun Fu; Xiao-Lei Qu; Pei-Zhe Sun; Yong Feng; Guang-Guo Ying (Water Research, 2026)

Contaminant migration in vadose zone beneath unregulated landfills with damaged geomembranes - Yu-Zhang Bi; Xin-Po Sun; Qi Zou; Zhe-Yuan Jiang; Xian-Lei Fu (Waste Management, 2026)

The Hongjianbingshan W–Li–(Be) deposit in the Beishan Orogenic Belt is not related to carboniferous magmatic–hydrothermal events: Insights from multi-mineral U-Pb and zinnwaldite Rb-Sr geochronology - Yong Yin; Heng-Feng Zhang; Zhuang Duan; Bing-Fei Yu; Heng Luo; Yan-Gang Fu; David R. Lentz; Tao Luo; Ke-Yu Ren; Zhe Ren; Hao Hu (Journal of Geochemical Exploration, 2026)

Intensification of extreme precipitation across the Tibetan Plateau and its climatic drivers over 1982−2020 - Yiming Song; Shiqin Xu; Dennis P. Lettenmaier; Hylke E. Beck; Xiaodong Chen; Zhongbo Yu; Ningpeng Dong; Qian Cao; Xiaolei Fu; Zhe Yang; Yuliang Zhang; Matthew F. McCabe (Global and Planetary Change, 2026)

How do moss-dominated biocrusts drive carbon sequestration under lithological constraints in karst soils? - Fang Wang; Yuanfeng Yang; Ze Li; Zhe Lin; Zhiyong Fu; Hongsong Chen; Yusong Deng (Plant and Soil, 2026)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

Numerical investigation of dynamic response in HDPE floating raft array for aquaculture: Coupled system analysis and sea trial evidence - Fei Fu; Zhe Hu; Xiaoying Zhang; Zhanbin Meng; Jianxing Yu (Ocean Engineering, 2025)

Enhancing water quality and sustainable resource utilization through an AIoT-enabled intelligent circular agriculture system - Hsiao-ling Lu; Yuan-Hsiou Chang; Tsai-Fu Chuang; Syuan-Ru Chen; Zhe-Dian Wu (Journal of Environmental Chemical Engineering, 2025)

Green hydrogen production via a photocatalyst-enabled optical fiber system: A promising route to net-zero emissions - Han Fu; Zhenhua Pan; Yen-Jung Sean Lai; Jirapat Ananpattarachai; Michael Serpa; Nora Shapiro; Zhe Zhao; Paul Westerhoff (Energy and Climate Change, 2025)

Cranial and middle ear structures of the Early Cretaceous mammal Origolestes (Spalacotherioidea, Trechnotheria, Mammalia) - Zhe-Xi Luo; Chang-Fu Zhou; Peishu Li; April I. Neander (Palaeobiodiversity and Palaeoenvironments, 2025)
In this study we offer a new analysis of the internal cranial structures and the middle ear of the Early Cretaceous spalacotherioid mammal Origolestes lii , from the Yixian Formation of Liaoning, China. This anatomical study is based on CT scanning of a three-dimensionally preserved skull of this taxon. Spalacotherioid mammals are a group in the trechnotherian clade that includes modern therians such as marsupials and placentals. Fossils of these Mesozoic stem therians can yield useful information on the evolutionary origin of modern therian traits. Because cranial fossils of Mesozoic stem therians in three-dimensional preservation are scarce, and also because the internal cranial structures used to be difficult to examine, before CT scanning of fossils became available, the internal cranial structure was rarely documented in detail. Our CT scanning and visualisation of the skull of Origolestes lii have revealed new anatomical information of the orbital and sphenoid regions of the braincase, for this group. This is helpful for interpreting the comparative morphology of the skull structure among Mesozoic mammals. Furthermore, this specimen is a rare fossil in that it has preserved the petrosal articulation of the incus, as well as the Meckelian-attached middle ear. Evidence from our CT rendering and digital re-articulation demonstrates that a connection of the malleus to the ossified Meckel’s cartilage still existed in Origolestes lii .

Crop rotation mitigates soil fungal diversity loss under warming or increased moisture - Zhibo Zhou; Keming Yang; David Tissue; Zhong Wei; Le Li; Zhe Tang; Lukuan Fu; Hanqin Li; Tingting Sheng; Hongwei Liu; Yingjun Zhang; Fengge Zhang (Agriculture, Ecosystems & Environment, 2025)

Investigating air-cushion effect in water-entry impact of notched-head blunt vehicles via the CFD-FEM coupling method - Zhe Zhang; Na-Na Yang; Wei Yang; Jin-Long Ju; Fu-Kui Gao; Wen-Hua Wu (Ocean Engineering, 2025)

Full-scale shake table testing method for seismic assessment of nonstructural elements using a universal testbed and a standard building-specific loading protocol - Yuteng Cao; Haoran Fu; Zhe Qu (Engineering Structures, 2025)

Salinity gradients induced multistability shifts of microbial communities in coastal tidal flats of Jiangsu Province - Jiating Fan; Linqiong Wang; Pengxiao Fu; Hong Ling; Zhe Zhao (Marine Biology, 2025)

Transgenerational effects and mechanisms of nano-SiO2 on pulmonary - Jiangliang Chu; Chengzhi Liu; Shuang Chen; Yifan Yang; Keyu Zhang; Yiping Fu; Beilei Yuan; Zhe Wang (Reproductive Toxicology, 2025)

Effects of agricultural inputs on soil virome-associated antibiotic resistance and virulence: A focus on manure, microplastic and pesticide - Wen-Jing Li; Timothy M. Ghaly; Sasha G. Tetu; Fu-Yi Huang; Hong-Zhe Li; Hua Li (Journal of Hazardous Materials, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

Pressure makes diamonds: Enhanced permeation resistance to petroleum hydrocarbons of a novel in-situ mixed wall material - Zhe-Yuan Jiang; Xian-Lei Fu; Yu-Ling Yang; Wei-Yi Xia; Min Wang; Heng Zhuang; Zi-Han Lu; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Neurotoxicity of chronic nano-neodymium oxide exposure in zebrafish: Behavioral and molecular insights - Bao-Fu Zhang; Xing-Zhe Wu; Jin-Xia Wang; Yan-Ling Liao; Zi-Xin Cai; Yiyun Liu; De-Sheng Pei (Journal of Hazardous Materials, 2025)

The autoignition characteristics of oxygen-in-ammonia blending fuel turbulent jet flame into high temperature co-flow - Meng Ji; Zhijun Wu; Zhe Kang; Quanbo Shang; Guanyu Zhang; Chaoqun Hu; Lezhong Fu; Yang Yu; Jun Deng; Liguang Li (Fuel, 2025)

Paeoniae Radix alba polysaccharide modulates gut microbiota to restore metabolites and promote the enteric nervous system development in colitis mice - Chao-Wen Zhang; Si-Zhe Shui; Shuang Liao; Yu-Chao Kuang; Dai-Zheng Yin; Yi Gu; Banaz Jalil; Michael Heinrich; Xing-Fu Chen; Zhong-Qiong Yin; Chun Wu; Xu Song; et al. (Food Bioscience, 2025)

Numerical investigation on prestressed shear key splice connections for onshore wind turbine foundations - Dongliang Zhang; Wantong Liu; Fei Wang; Zhe Yu; Xiangguo Wu; Tianhao Li; Kun Fu; Anish Thapa Magar; Hyeon-Jong Hwang; Xiangping Xian (Engineering Structures, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Removal of organic pollutants from secondary treated effluent of a chemical industrial park using synchronized oxidation-adsorption (SOA), coagulation and Fenton processes: A comparison study - Anqi Feng; Yuzhu Jia; Kaitao Zhang; Zhe Tian; Sufeng Tian; Xueke Wang; Yongzhi Chi; Cuilian Fu (Journal of Environmental Chemical Engineering, 2025)

Mid-latitude climatic oscillation during the late Ediacaran ice age - Jiajun Wang; Ruimin Wang; Zhe Qi; Shihao Fu; Gang Wang; Bing Shen (Global and Planetary Change, 2025)

Physically consistent data-driven optimal sequencing strategy for variable speed pumps in large building chiller plants - Zhe Chen; Jing Zhang; Fu Xiao; Kan Xu; Yongbao Chen (Building and Environment, 2025)

Study on the lock-in delay coefficient in the mathematical model of transversal vortex-induced vibration for a rigid circular cylinder - Zhe Xu; Deyi Fu; Lei Jin; Shiqiao Gao (Ocean Engineering, 2025)

SEBS-amended in-situ mixed wall material for diesel-contaminated groundwater management - Zhe-Yuan Jiang; Xian-Lei Fu; Fei Jin; Chi Che; Zhong-Yuan Li; Guojun Cai; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Improved bending performance of 3D-printed continuous fiber reinforced composite topological structure by a crossing-lap path designing - Yueyan Huang; Zhe Yang; Wanyi Liu; Zhongsen Zhang; Kunkun Fu; Yan Li (Engineering Structures, 2025)

Enhancing containment performance of geosynthetic clay liner to bauxite liquor via composite polymer amendment - Xian-Lei Fu; Zhe-Yuan Jiang; Min Wang; Hao Ni; Yan-Jun Du (Engineering Geology, 2025)

Human presence in the southeastern Tibetan Plateau after the Last Glacial Maximum - Jia-Jing Wang; Pei-Yang Tan; Yue Feng; Zhe-Xuan Zheng; Yu-Jie Guo; Jia-Ning He; You-Ping Wang; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Water erosion risk assessment and predictive modelling for cultural heritage under climate change: A case study of the Great Wall in the Yellow River Basin, China - Tianlian Wang; Zhiyuan Fu; Shijie Zhang; Zhe Li (Journal of Cleaner Production, 2025)

Multi-modal image fusion of visible and infrared for precise positioning of UAVs in agricultural fields - Xiaodong Liu; Meibo Lv; Chenyuhao Ma; Zhe Fu; Lei Zhang (Computers and Electronics in Agriculture, 2025)

The role of ATG7-mediated ferroptosis in formaldehyde-induced ovarian injury in rats - Kun Mao; Hao-zhe Yan; Jia-qi Yang; Zi-xin Yin; Xin-qi Gao; Hao-fu Liu; Heng Su; Yuan-yuan Geng; Pan Ge; Dang-xia Zhou (Reproductive Toxicology, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Vibration reduction characteristics of steel-rubber periodic damper based on finite-domain quasi-surface wave effect - Yu-xuan Qin; Yang Tang; Zhe Zhao; Hai-chao Li; Fu-zhen Pang; Zi-teng Mao (Ocean Engineering, 2025)

Forest litter decomposition stimulates heterotrophic nitrogen fixation by driving diazotrophic community interactions - Chang Pan; Shuikuan Bei; Zhe Hua; Mengtian Zhou; Zichen Wang; Ruoxian Fu; Xiaogang Li (Biology and Fertility of Soils, 2025)

In situ regeneration of phenol-saturated activated carbon fiber via an electro-permanganate process - Zhen Liu; Lang Liu; Yiwei Fu; Huan He; Chuanliang Zhao; Xiaodi Duan; Bangxing Ren; Zhe Zhang; Shaochun Yuan; Yao Chen (Journal of Water Process Engineering, 2025)

Optimization of mechanical properties and finite element simulation analysis of hollow fiber membranes in gas-liquid membrane separation technology - Zhengda Lin; Yihe Wang; Zhe Fu; Dan Zhong; Xingwei Du; Jun Zhang (Desalination, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

Revealing the mobilization and age of estuarine dissolved organic matter during floods using radiocarbon and molecular fingerprints - Zhao Liang Chen; Yuanbi Yi; Ruanhong Cai; Zhe-Xuan Zhang; Wenzhao Liang; Wenjing Fu; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; et al. (Water Research, 2025)

An AI-enabled optimal control strategy utilizing dual-horizon load predictions for large building cooling systems and its cloud-based implementation - Ziwei Xiao; Jing Zhang; Fu Xiao; Zhe Chen; Kan Xu; P.M. So; K.T. Lau (Energy and Buildings, 2025)

Creep constitutive model of yellow sandstone under coupling action of unloading and wet-dry cyclic damage - Zhe Qin; Zhen Liu; Run-chang Zhang; Hou-li Fu (Journal of Mountain Science, 2025)

Maltodextrin vitamin E succinate: A novel antioxidant emulsifier for formulating functional nanoemulsions - Xiang Luo; Yuanyuan Chen; Zhe Jiang; Hongze Wu; David Julian McClements; Chang Zhang; Yanyan Zhou; Hongliang Fu; Xuguang Yin; Wenna Huang; Zhixin Wang; Lemao Yu; et al. (Food Chemistry, 2025)

Feasibility analysis of expanding winter rapeseed northwards in China - Junqiang Fan; Gang Yang; Junyan Wu; Yuanyuan Pu; Lijun Liu; Li Ma; Tingting Fan; Wangtian Wang; Yahong Zhang; Jianming Lei; Qiang Li; Xianfei Hou; et al. (Agricultural and Forest Meteorology, 2025)

Unpacking greenwashing: The impact of environmental attitude, proactive strategies, and network embeddedness on corporate environmental performance - Fu Huang; Jiawei Wu; Zhanglan Wu; Weiqiong Fu; Ping Guo; Zhe Zhang; Farina Khan (Journal of Environmental Management, 2025)

Insight into the impact of various processing stages on metabolites and flavors in jujube jam - Jun Liu; Zhe Wu; Jiamin Zhu; Xiaoyu Fu; Mengnan Wang; Jun Xing; Xinzheng Qin; Yixian Tu; Yun-Guo Liu (Food Research International, 2025)

Long-term trend of the tropical cyclone translation speed over the western North Pacific with track change - Kai-Jie Fu; Yi‑Peng Guo; Zhe‑Min Tan (Climate Dynamics, 2025)

Health impacts of climate resilient city development: Evidence from China - Kai-yang Fu; Yu-zhe Liu; Xin-yu Lu; Bin Chen; You-hua Chen (Sustainable Cities and Society, 2024)

SCARF: A new algorithm for continuous prediction of biomass dynamics using machine learning and Landsat time series - Yingchun Fu; Runhao Li; Zhe Zhu; Yufei Xue; Hu Ding; Xinyu Wang; Jiaming Na; Weijie Xia (Remote Sensing of Environment, 2024)

Antibiotic resistance at environmental multi-media interfaces through integrated genotype and phenotype analysis - Chen-Xi Fu; Chen Chen; Qian Xiang; Yi-Fei Wang; Lu Wang; Feng-Yuan Qi; Dong Zhu; Hong-Zhe Li; Li Cui; Wei-Li Hong; Matthias C. Rillig; Yong-Guan Zhu; et al. (Journal of Hazardous Materials, 2024)

Occurrence and fate of five representative neonicotinoid insecticides across different wastewater treatment plants and the impact on receiving water bodies - Yuhan Ke; Wanbing Zheng; Di Tian; Siyu Ke; Shuna Fu; Zhe Zhang; Yue Xie; Junyu Zhu; Bangxing Ren; Chao Zhang; Xiaohui Yi; Mingzhi Huang (Environmental Research, 2024)

Substructural shake table testing for nonstructural elements of various damage sensitivity in a fixed-base and a base-isolated building - Haoran Fu; Yuteng Cao; Zhe Qu (Engineering Structures, 2024)

Functional characterization of Arabidopsis hydroxynitrile lyase in response to abiotic stress and the regulation of flowering time - Lei Xue; Duo Bu; Jiangyan Fu; Zhe Zhou; Meng Gao; Ren Wang; Sheng Xu (Molecular Biology Reports, 2024)

A review of ethical considerations for the medical applications of brain-computer interfaces - Zhe Zhang; Yanxiao Chen; Xu Zhao; Wang Fan; Ding Peng; Tianwen Li; Lei Zhao; Yunfa Fu (Cognitive Neurodynamics, 2024)

Molecular cloning and functional characterization of eight galectin genes from Takifugu obscurus - Ying Huang; Sheng-Hao Du; Li-Fan Cui; Fu-Hui Jiang; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Research progress in solar-assisted crude oil absorbing materials - Jialong Fu; Wanlin Xu; Feiyu Cao; Qiang Wang; Zhe Li; Hao Li; Xuying Liu; Wentao Liu (Journal of Environmental Chemical Engineering, 2024)

Direct measurement for hand-transmitted vibration of human fingers-hand-arm system in the zero-gravity environment - Hao Fu; Yang Yu; Yang Chen; Zhe Wang; Tingting Wu (Advances in Space Research, 2024)

Numerical Simulation and On-Site Measurement of Dynamic Response of Flexible Marine Aquaculture Cages - Xiaoying Zhang; Fei Fu; Jun Guo; Hao Qin; Qian Sun; Zhe Hu (Journal of Marine Science and Engineering, 2024)
Flexible cages are widely used in marine aquaculture, yet their mechanical features in extreme seas are still unclear. This study proposes a numerical algorithm to solve the coupled response of the multiple cage systems. The net and mooring lines are modeled using the lumped-mass model, while the flexible floating collar system is assessed with the large-deformation FEM model, and the two models are coupled through an iterative scheme. Sea trials are conducted, and the motion of the cage is obtained using an image processing technique, which validates the numerical algorithm. Using the proposed numerical algorithm, a series of simulations are performed to investigate the response of flexible cages in extreme seas. Motions, line tensions, and structural sectional forces are studied, and the effects of factors such as the wavelength of incident waves and the diameter of collar pipes are investigated.

Lithospheric electrical structure and geodynamic model of the red river fault zone and its adjacent areas in southwest China: Constraints from 3-D magnetotelluric imaging - Zhe Yun; Zhiguo An; Qingyun Di; Yilang Zhang; Pengfei Liang; Changmin Fu (Journal of Asian Earth Sciences, 2024)

Biomechanical behavior of grass roots at different gauge lengths - Jiangtao Fu; Zhe Zhou; Hong Guo; Jimei Zhao; Dongmei Yu; Jie Wu; Xiasong Hu (Journal of Mountain Science, 2024)

Evolution of volcanic activity and its impact on continental weathering, paleoproductivity, and runoff during the early Aptian in southern Tibet (eastern Tethys): Implications for regional to global environmental perturbations - Ying Nie; Xiugen Fu; Ahmed Mansour; Shengqiang Zeng; Mohamed S. Ahmed; Fangzhi Hu; Fei Lin; Zhe Qi; Qiangwang Wu; Manuel Rigo (Sedimentary Geology, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Research on Sea Trial Techniques for Motion Responses of HDPE Floating Rafts Used in Aquaculture - Fei Fu; Xiaoying Zhang; Zhe Hu; Yan Li; Lihe Wang; Jianxing Yu (Journal of Marine Science and Engineering, 2024)
The innovative aquaculture equipment known as high-density polyethylene (HDPE) floating rafts has gained popularity among fishermen in the southeast coastal regions of China. Compared to deep-water anti-wave fish cages, the construction costs of HDPE floating rafts are 50% to 75% less. There is a dearth of comprehensive publicly available records of HDPE floating rafts sea trial data, despite substantial numerical studies on the motion response of aquaculture fish cages and scale model experiments under controlled-wave conditions. This study involves sea trial techniques under operational and extreme environmental conditions for motion responses of HDPE floating rafts, presents a comprehensive procedure for sea trials of HDPE floating rafts, summarizes the issues encountered during the trials, and suggests solutions. Using MATLAB for independent programming, motion videos and photos collected from the sea trials are processed for image capture, yielding the original time history curve of vertical displacement. Based on the sea trials’ data, including motion displacement, acceleration, mooring line force, overall deformation patterns, and current and wave data, recommendations are provided for the design and layout of HDPE floating rafts. Based on the Fast Fourier Transform (FFT) method for spectral analysis, the influence of interference items on the observational data is eliminated; the rationality of the observational data is verified in conjunction with the results of the Gabor Transform. This study offers a scientific analytical method for the structural design and safe operation of HDPE floating rafts and provides a reference for subsequent numerical simulations.

Bi-2-(2-phenethyl)chromone derivatives from agarwood of Aquilaria filaria in the Philippines - Hong-Run Yang; Hao Wang; Pei Wang; Fang-Zheng Liu; Hong-Xing Chai; Cai-Hong Cai; Li Yang; Jing-Zhe Yuan; Bei Jiang; Wen-Li Mei; Hao-Fu Dai (Phytochemistry, 2024)

A geometric variation method to extract rock strength parameters via uniaxial compression testing - Zhe Li; Zhen-Qi Yang; Meng Fu; Gao-Feng Zhao (International Journal of Rock Mechanics and Mining Sciences, 2024)

Polydopamine-immobilized lysozyme for the fabrication of antibacterial films and its application in the preservation of fresh pork - Aichun Lv; Guangsen Fan; Zhe Yang; Xinyue Zhang; Muhammad Moeid Khan; Xing Fu (Food Packaging and Shelf Life, 2024)

Unveiling the effect of H2S concentration in CH4 hydrate formation and growth: A molecular dynamics study - Xianwu Jing; Li Zhou; Ziyi Fu; Qian Huang; Zhe Zhang (Chemical Engineering Journal, 2024)

How does energy utilization affect rural sustainability development in traditional villages? Re-examination from the coupling coordination degree of atmosphere-ecology-socioeconomics system - Qikang Zhong; Hongpeng Fu; Jiale Yan; Zhe Li (Building and Environment, 2024)

Hot spots and trends in microbial disease research on cultural heritage: a bibliometric analysis - Weilin Chen; Baorong Fu; Fang Ma; Zhe He; Ming Li (Environmental Science and Pollution Research, 2024)

Dynamics collision risk evaluation and early alert in busy waters: A spatial-temporal coupling approach - Yang Chen; Zhao Liu; Mingyang Zhang; Hongchu Yu; Xiuju Fu; Zhe Xiao (Ocean Engineering, 2024)

Hi-Tag: a simple and efficient method for identifying protein-mediated long-range chromatin interactions with low cell numbers - Xiaolong Qi; Lu Zhang; Qiulin Zhao; Peng Zhou; SaiXian Zhang; Jingjin Li; Zhuqing Zheng; Yue Xiang; Xueting Dai; Zhe Jin; Yaobang Jian; Xinyun Li; et al. (Science China Life Sciences, 2024)

ORP-Byte: A multi-object tracking method of pigs that combines Oriented RepPoints and improved Byte - Jisheng Lu; Zhe Chen; Xuan Li; Yuhua Fu; Xiong Xiong; Xiaolei Liu; Haiyan Wang (Computers and Electronics in Agriculture, 2024)

Outer membrane vesicles of avian pathogenic Escherichia coli induce necroptosis and NF-κB activation in chicken macrophages via RIPK1 mediation - Zhe Li; Wenbin Shang; Ting Mei; Dandan Fu; Feng Xi; Ying Shao; Xiangjun Song; Zhenyu Wang; Kezong Qi; Jian Tu (Research in Veterinary Science, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

CO2 capture using low silica X zeolite synthesized from low-grade coal gangue via a two-step activation method - Chenghao Liu; Fu Rao; Yalou Guo; Zhe Lu; Wenkang Deng; Guobiao Li; Hui Zhang; Tao Qi; Guoping Hu (Journal of Environmental Chemical Engineering, 2024)

Effect of relative humidity on the desulfurization performance of calcium-based desulfurizer - Juan Lǖ; Yu Fu; Haiyan Yu; Huan Wang; Zhe Wang; Haiyan Chen (Journal of Environmental Sciences, 2024)

Self-Healing and shape memory reconfigurable Poly(urethane-urea-amide) elastomers containing multiple dynamic bonds for improving performance of 4D printout - Zhen Li; Ziwei Cao; Qianlong Zhao; Shuxiang Mei; Yuancheng Zhang; Wei Zhao; Xin Li; Xiaomeng Zhang; Zhe Cui; Peng Fu; Xinchang Pang; Minying Liu (Chemical Engineering Journal, 2024)

Modelling sludge dewatering in treatment reed bed considering sludge deposit formation - Yu Zhe Huong; Yee Yong Tan; Fu Ee Tang; Agus Saptoro (Modeling Earth Systems and Environment, 2024)
The accumulation of sludge deposits is a crucial factor in the dewatering efficiency of sludge treatment reed bed (STRB). This paper presents an improved one-dimensional process-based mathematical model to simulate the dewatering mechanism in STRBs, in which the compressible cake filtration (CCF) theory was implemented to simulate the sludge deposits accumulation on the surface of the reed bed, while the varying sludge deposit thickness was accounted for using the moving mesh method. The proposed model also included the dual porosity variably saturated flow model and the Penman–Monteith equation to describe the dewatering through gravity drainage and evapotranspiration, respectively. The results from the model were validated with experimental data from laboratory-scale STRBs treating septage. The simulation results showed that considering the sludge deposit layer as a specific flow resistance effectively avoids the overprediction of water infiltration rate in the reed bed. The predicted results showed excellent agreement with the actual data, where only five cases of the root mean square error were above 10% compared to the average effluent flux. Further, the effect of evapotranspiration was found to be insignificant within a short-term simulation. The consideration of the influence of sludge deposit formation on drainage dewatering using the CCF model and moving mesh model has delivered a more robust simulation for sludge dewatering in STRBs, and the proposed model is capable of facilitating the understanding of the interactions between the sludge dewatering in STRB with respect to the bed characteristics, hydraulic load, and solid load.

Iron oxide–apatite deposits form from hydrosaline liquids exsolved from subvolcanic intrusions - Xin-Fu Zhao; Li-Ping Zeng; Wang Liao; Yi-Zhe Fan; Albert H. Hofstra; Poul Emsbo; Hao Hu; Guang Wen; Jian-Wei Li (Mineralium Deposita, 2024)

Hydraulic conductivity and microscopic properties of polyanionic cellulose and microscale zero-valent iron amended sand/bentonite backfills exposed to dichloromethane solution - Heng Zhuang; Guang-Yu Yang; Xian-Lei Fu; Zhe-Yuan Jiang; Yan-Jun Du (Science of The Total Environment, 2024)

Wilson cycles of the Zagros fold and thrust belt: A comprehensive review - Xiaofei Fu; Zhiqiang Feng; Faqiang Zhang; Zhongmin Zhang; Jinrui Guo; Zhe Cao; Ting Kor; Ming Cheng; Jianzhao Yan; Yu Zhou (Journal of Asian Earth Sciences, 2024)

Micro formation mechanism of oil–water inversion in reservoirs based on water film theory—An example from the Dawangzhuang Oilfield in Bohai Bay Basin - Xiao Hu; Longchuan Pu; Aihua Ran; Jun Xie; Fengqun Li; Yuzong Cheng; Suhua Zhang; Zhe Li; Qiongyao Pu; Jialin Fu (Fuel, 2024)

Photocurable 3D-printed AgNPs/Graphene/Polymer nanocomposites with high flexibility and stretchability for ECG and EMG smart clothing - Jia-Wun Li; Ho-Fu Chen; Yu-Zhe Liu; Jui-Hsin Wang; Ming-Chang Lu; Chih-Wei Chiu (Chemical Engineering Journal, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Long-term seawall barriers lead to the formation of an urban coastal lagoon with increased antibiotic resistome - Shu-Yi-Dan Zhou; Kai Yang; Roy Neilson; Hu Li; Hong-Zhe Li; Yan-Yan Zhou; Juxiu Liu; Jian-Qiang Su; Fu-Yi Huang (Journal of Environmental Management, 2024)

Ultrasonic vibration enabled under-liquid forming of metallic glasses - Xin Li; Luyao Li; Sajad Sohrabi; Jia’nan Fu; Zhen Li; Zhe Chen; Rongce Sun; Yu Zhang; Jinbiao Huang; Heting Zhang; Jian Zhu; Xiangyan Chen; et al. (Science Bulletin, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Fast nitrate formation aloft supported by typical synoptic weather patterns and complex terrain in the North China Plain - Chuang Qin; Xianyi Sun; Zhe Yin; Zhihao Yang; Xiao Fu (Atmospheric Environment, 2024)

Bacterial glycerol tetraethers as a potential tool to trace marine methane cycling - Zhe‐Xuan Zhang; Jiwei Li; Hongxuan Lu; Huan Yang; Yige Zhang; Yongjie Tang; Meiyan Fu; Xiaotong Peng (Limnology and Oceanography, 2024)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial lipids that can be preserved in sedimentary archives for tens of millions of years and are ubiquitous in diverse environments, including cold seep systems. Their potential implications for detecting methane activity in deep time are, however, hampered by the multiple sources of brGDGTs in cold seeps and the lack of evidence of their stable carbon isotopes. Here, we show that brGDGTs in cold seeps are characterized by depleted stable carbon isotopic compositions of the alkyl moieties (δ 13 C = −32.9‰ to −82.7‰), indicating a methane metabolizing community origin, which is supported by the association between 16S rRNA genes and brGDGTs. We further identify unique seep‐derived brGDGT signals from the global published dataset by a tree‐based machine‐learning algorithm. This trained model, named light gradient‐boosting machine classification for paleoSEEP (GBM_SEEP), is further applied on a paleorecord across the Paleocene–Eocene Thermal Maximum (PETM), which suggests potential methane emission events during the PETM recovery phase. Collectively, our study links brGDGT production in cold seeps with methane metabolizing communities and provides a potential strategy to capture significant methane emission events using the machine‐learning model, which warrants further investigation.

Deep utilization of salinity gradient energy between concentrated seawater and river water by multi-stage reverse electrodialysis - Zhi-Yuan Guo; Wei-Zhe Cui; Zhi-Yong Ji; Kaniki Tumba; Jing Wang; Liu-Jia Fu; Zhao-Xiang Zhang; Jie Liu; Ying-Ying Zhao; Zhong-De Zhang; Jun-Sheng Yuan (Desalination, 2023)

Modeling and optimization of Graphene Oxide (GO) membranes for nanofiltration with artificial neural networks - Haodong Yang; Zhe Chen; Yong Li; Lei Yao; Geming Wang; Quanrong Deng; Ping Fu; Shenggao Wang (Journal of Water Process Engineering, 2023)

New insights into potential effects of solar activity on the oxygen isotope composition of modern speleothems: Observations from Jiguan Cave, central China II - Xiaomin Chen; Xiuyang Jiang; Xianguo Wang; Jingyao Zhao; Zhe Sun; Yidong Li; Zhimao Ye; Jianrong Cai; Xin Fu; Yanzhi Xu; Yan Yang (Journal of Hydrology, 2023)

Dissolved black carbon incorporating with ferric minerals promoted photo-Fenton-like degradation of triclosan in acidic conditions - Ziyan Zhou; Hao Wu; Boming Fu; Zhe Wang; Ran Hong; Liuqing Huang; Xinyue Gu; Cheng Gu; Xin Jin (Journal of Hazardous Materials, 2023)

Oral administration of sophoricoside (SOP) inhibits neuronal damage and neuroinflammation to curb neurodegeneration in Parkinson's disease - Hefei Wang; Dewei He; Zhe Li; Xiyu Gao; Shuo Yang; Mingchi Cui; Bojian Ye; Bingxu Huang; Shoupeng Fu; Dianfeng Liu (Chemico-Biological Interactions, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Comparative genomics provides insights into the phylogeny and environmental adaptations of Peritrichia (Protista, Ciliophora) – A potential resource for environmental pollution control and bioremediation - Ying Zhang; Huan Dou; Yu Fu; Fasheng Liang; Zhe Wang; Alan Warren; Lifang Li (Molecular Phylogenetics and Evolution, 2023)

Lipopolysaccharide accelerates tryptophan degradation in the ovary and the derivative kynurenine disturbs hormone biosynthesis and reproductive performance - Jie Shen; Weimin Zhao; Juanru Cheng; Jinhua Cheng; Lei Zhao; Chaohui Dai; Yanfeng Fu; Bixia Li; Zhe Chen; Deshun Shi; Hui Li; Yanfei Deng (Journal of Hazardous Materials, 2023)

An integrated fuzzy AHP and fuzzy TOPSIS approach for screening backfill materials for contaminant containment in slurry trench cutoff walls - Xian-Lei Fu; Hao Ni; Annan Zhou; Zhe-Yuan Jiang; Ning-Jun Jiang; Yan-Jun Du (Journal of Cleaner Production, 2023)

Late Mesoproterozoic to early Neoproterozoic metamorphic history of the North Wulan terrane, NW China: New constraints on the evolution of Rodinia - Jiahao He; Xiucai Li; Manlan Niu; Chris Yakymchuk; Chen Li; Zhen Yan; Changlei Fu; Zhe Heng (Journal of Asian Earth Sciences, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

Application of stable isotope and mineral element fingerprint in identification of Hainan camellia oil producing area based on convolutional neural networks - Jiashun Fu; Junhao Wang; Zhe Chen; Zhuowen Deng; Hanggui Lai; Liangxiao Zhang; Yong-Huan Yun; Chenghui Zhang (Food Control, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

In situ prepared Chlorella vulgaris–supported nanoscale zero-valent iron to remove arsenic (III) - Tingting Yue; Yuankun Yang; Shu Chen; Jun Yao; Huili Liang; Liang Jia; Kaibin Fu; Zhe Wang (Environmental Science and Pollution Research, 2023)

Designing Er3+ Single-doped ternary sulfide for highly efficient upconversion luminescence under 1550 nm excitation - Hong Wang; Zhe He; Ke Cai; Limin Wei; Yang Xu; Yao Fu; Mingming Xing; Ying Tian (Chemical Engineering Journal, 2023)

Development of an Antarctic krill oil based self-microemulsion drug delivery system and its enhancement of bioaccessibility for curcumin - Dong-wen Fu; Ye Tian; Zi-han Wang; Jin-zhe Li; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Bioscience, 2023)

Long-term effects of phosphorus deficiency on one-stage partial nitrification-anammox system and recovery strategies - Liang Zhang; Zhe Tian; Yunzhi Qian; Fuqiang Chen; Yu-You Li; Xueke Wang; Cuilian Fu; Yongzhi Chi (Journal of Cleaner Production, 2023)

A two-step three dimensional marine magnetotelluric inversion method with considering rugged seafloor topography: Synthetic studies - Pengfei Liang; Qingyun Di; Changmin Fu; Ruo Wang; Qihui Zhen; Zhe Yun; Jiagang Zhang (Science China Earth Sciences, 2023)

Identification and hepatoprotective activity of total glycosides of paeony with high content of paeoniflorin extracted from Paeonia lactiflora Pall - Lin Peng; Zhe Ma; Wenhui Chu; Peisi Jiang; Yongqian Fu; Pan Wang (Food and Chemical Toxicology, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Paracoccus marinaquae sp. nov., isolated from coastal water of the Yellow Sea - Hua-Peng Xue; Zi-Yue Fu; Wei He; Lei Wang; Wen-Jun Li; Ai Hua Zhang; Jian-Ke Huang; Dao-Feng Zhang; Zhe Zhao (Archives of Microbiology, 2023)

Impacts of climate change on future hurricane induced rainfall and flooding in a coastal watershed: A case study on Hurricane Harvey - Xudong Li; Dan Fu; John Nielsen-Gammon; Sudershan Gangrade; Shih-Chieh Kao; Ping Chang; Mario Morales Hernández; Nathalie Voisin; Zhe Zhang; Huilin Gao (Journal of Hydrology, 2023)

Design and syntheses of Cu–Fe3O4@Fe electrode with needle-like structure and electric field potential: Remediation of nitrate contamination and action in protein wastewater - Zhe Zhang; Gang Xin; Yuzhen Pan; Zhen Chen; Yawen Sun; Chengzheng Wang; Shuyi Li; Linsen Wei; Zibi Fu; Wei Ma (Journal of Cleaner Production, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

A microscale regulation strategy for strong, tough, and efficiently self-healing energetic adhesives - Jing Yang; Xin Zhou; Junqing Yang; Jiaoyang Chen; Zhe Sun; Yuhang Cheng; Lin Yang; Hui Wang; Guangpu Zhang; Jiajun Fu; Wei Jiang (Chemical Engineering Journal, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Investigation of migration rule of rainwater for sponge city roads under different rainfall intensities - Zhe Qin; Yujing Yao; Jingwei Zhao; Houli Fu; Sheng Zhang; Liyuan Qiu (Environmental Geochemistry and Health, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Quantifying the associations of the air pollutant SO2 on outpatient visits for conjunctivitis in Hangzhou, China - Zhijian Chen; Qiuli Fu; Lizhi Wu; Peiwei Xu; Dandan Xu; Xuejiao Pan; Xiaoming Lou; Xiaofeng Wang; Ke Yao; Zhe Mo (Environmental Science and Pollution Research, 2022)

Chronology, geochemical characteristics, and tectonic implications of a Triassic complex in the Rongma Area, Southern Qiangtang, Tibet - Zheng-Zhe Fan; Quan Wang; Xian Chen; Gen-Hou Wang; Yue Fu; Gui-Juan Guo (International Journal of Earth Sciences, 2022)

A new picrotoxane-type sesquiterpene from Dendrobium nobile Lindl - Pei Wang; Xin Chen; Cai-Hong Cai; Fan-Dong Kong; Sheng-Zhuo Huang; Jing-Zhe Yuan; Xing-Lian Xu; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2022)

Extreme Cold Events from East Asia to North America in Winter 2020/21: Comparisons, Causes, and Future Implications - Xiangdong Zhang; Yunfei Fu; Zhe Han; James E. Overland; Annette Rinke; Han Tang; Timo Vihma; Muyin Wang (Advances in Atmospheric Sciences, 2022)

The beneficial roles of poisonous skin secretions in survival strategies of the odorous frog Odorrana andersonii - Naixin Liu; Buliang Meng; Wenxin Bian; Meifeng Yang; Longjun Shu; Yixiang Liu; Zhe Fu; Yinglei Wang; Ying Wang; Xinwang Yang (The Science of Nature, 2022)

Optimal array layout of cylindrical baffles to reduce energy of rock avalanche - Yu-zhang Bi; Dong-po Wang; Xian-lei Fu; Yi-xiong Lin; Xin-po Sun; Zhe-yuan Jiang (Journal of Mountain Science, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Quantifying glacial elevation changes in the central Qilian Mountains during the early 21st century - Qi-bing Zhang; Cao-hu Mo; Di Zhao; Zong-li Jiang; Zhe-fu Chen; Kun-peng Wu; Zhen Zhang (Journal of Mountain Science, 2021)

Creep Properties of Altered Rock Subjected to Water Influx-Lost Cycles - Xuxin Chen; Zhe Qin; Houli Fu (Geotechnical and Geological Engineering, 2021)

Increasing mortality caused by chronic obstructive pulmonary disease (COPD) in relation with exposure to ambient fine particulate matters: an analysis in Southeastern China - Zhijian Chen; Qiuli Fu; Guangming Mao; Lizhi Wu; Peiwei Xu; Dandan Xu; Zhifang Wang; Xuejiao Pan; Yuan Chen; Xiaoming Lou; Zhe Mo; Xiaofeng Wang; et al. (Environmental Science and Pollution Research, 2021)

The common risk factors for progression and mortality in COVID-19 patients: a meta-analysis - Li Zhang; Jie Hou; Fu-Zhe Ma; Jia Li; Shuai Xue; Zhong-Gao Xu (Archives of Virology, 2021)

Bisphenol A induces ovarian cancer cell proliferation and metastasis through estrogen receptor-α pathways - Chen Sang; Yu Song; Tong-wang Jin; Shuo Zhang; Linyan Fu; Yi Zhao; Xinxin Zou; Zhe Wang; Hui Gao; Sijin Liu (Environmental Science and Pollution Research, 2021)

Blocking the JAK2/STAT3 and ERK pathways suppresses the proliferation of gastrointestinal cancers by inducing apoptosis - Xi Wang; Chunyan Dai; Yifei Yin; Lin Wu; Weiyang Jin; Yufei Fu; Zhe Chen; Ke Hao; Bin Lu (Journal of Zhejiang University-SCIENCE B, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Combining targeted sequencing and ultra-low-pass whole-genome sequencing for accurate somatic copy number alteration detection - Junfeng Fu; Weihua Guo; Cheng Yan; Zhenyang Lv; Yu Wang; Ze Wang; Zhe Fan; Ting Lei (Functional & Integrative Genomics, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Dinitrogen (N2) pulse emissions during freeze-thaw cycles from montane grassland soil - Xing Wu; Zhe Chen; Ralf Kiese; Jin Fu; Silvia Gschwendter; Michael Schloter; Chunyan Liu; Klaus Butterbach-Bahl; Benjamin Wolf; Michael Dannenmann (Biology and Fertility of Soils, 2020)
Short-lived pulses of soil nitrous oxide (N 2 O) emissions during freeze-thaw periods can dominate annual cumulative N 2 O fluxes from temperate managed and natural soils. However, the effects of freeze thaw cycles (FTCs) on dinitrogen (N 2 ) emissions, i.e., the dominant terminal product of the denitrification process, and ratios of N 2 /N 2 O emissions have remained largely unknown because methodological difficulties were so far hampering detailed studies. Here, we quantified both N 2 and N 2 O emissions of montane grassland soils exposed to three subsequent FTCs under two different soil moisture levels (40 and 80% WFPS) and under manure addition at 80% WFPS. In addition, we also quantified abundance and expression of functional genes involved in nitrification and denitrification to better understand microbial drivers of gaseous N losses. Our study shows that each freeze thaw cycle was associated with pulse emissions of both N 2 O and N 2 , with soil N 2 emissions exceeding N 2 O emissions by a factor of 5–30. Increasing soil moisture from 40 to 80% WFPS and addition of cow slurry increased the cumulative FTC N 2 emissions by 102% and 77%, respectively. For N 2 O, increasing soil moisture from 40 to 80% WFPS and addition of slurry increased the cumulative emissions by 147% and 42%, respectively. Denitrification gene cnorB and nosZ clade I transcript levels showed high explanatory power for N 2 O and N 2 emissions, thereby reflecting both N gas flux dynamics due to FTC and effects of different water availability and fertilizer addition. In agreement with several other studies for various ecosystems, we show here for mountainous grassland soils that pulse emissions of N 2 O were observed during freeze-thaw. More importantly, this study shows that the freeze-thaw N 2 pulse emissions strongly exceeded those of N 2 O in magnitude, which indicates that N 2 emissions during FTCs could represent an important N loss pathway within the grassland N mass balances. However, their actual significance needs to be assessed under field conditions using intact plant-soil systems.

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

miR-346-3p promotes osteoclastogenesis via inhibiting TRAF3 gene - Yingji Mao; Yu Chen; Yingxiao Fu; Jingjing Guan; Mengxiang Liang; Yansong Zhu; Fugen Yang; Feixiang Li; Zhe Zhang; Chuanfeng Wan; Pinghui Zhou (In Vitro Cellular & Developmental Biology - Animal, 2020)

Simplified procedure for laterally loaded drilled shafts in spatially random clays - Zhe Luo; Zhongyang Wu; Longlong Fu (Marine Georesources & Geotechnology, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Identification and characterization of a novel gene-encoded antioxidant peptide obtained from amphibian skin secretions - Ying Wang; Xiaoqing Cao; Zhe Fu; Siyuan Wang; Xiaojie Li; Naixin Liu; Zhuo Feng; Meifeng Yang; Jing Tang; Xinwang Yang (Natural Product Research, 2020)

Magnetotail dipolarization fronts and particle acceleration: A review - Huishan Fu; Elena E. Grigorenko; Christine Gabrielse; Chengming Liu; San Lu; K. J. Hwang; Xuzhi Zhou; Zhe Wang; Fang Chen (Science China Earth Sciences, 2020)

The synergetic effect of pelvic rotation and X-ray offset on radiographic angles of the acetabular cup - Jing-Xin Zhao; Xiu-Yun Su; Zhe Zhao; Ruo-Xiu Xiao; Guo-Fei Sun; Li-Cheng Zhang; Pei-Fu Tang (Medical & Biological Engineering & Computing, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Effects of different potassium fertilizers on cadmium uptake by three crops - Kang Wang; Guiping Fu; Yao Yu; Yanan Wan; Zhe Liu; Qi Wang; Jingsuo Zhang; Huafen Li (Environmental Science and Pollution Research, 2019)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Cross-sectional Study: Relationship Between Serum Selenium and Hypertension in the Shandong Province of China - Guanrui Wu; Zhe Li; Wen Ju; Xiaomei Yang; Xiaofeng Fu; Xibao Gao (Biological Trace Element Research, 2018)

Association of Elements with Schizophrenia and Intervention of Selenium Supplements - Zhe Li; Yumei Liu; Xia Li; Wen Ju; Guanrui Wu; Xiaomei Yang; Xiaofeng Fu; Xibao Gao (Biological Trace Element Research, 2018)

Aestuarium zhoushanense gen. nov., sp. nov., Isolated from the Tidal Flat - Xiao-Yun Yu; Jing-Yu Zhai; Ge-Yi Fu; Xia Shen; Zhe Zhao; Min Wu; Xin-Qi Zhang (Current Microbiology, 2017)

Synergistic effects of temperature and humidity on the symptoms of COPD patients - Zhe Mu; Pei-Li Chen; Fu-Hai Geng; Lei Ren; Wen-Chao Gu; Jia-Yun Ma; Li Peng; Qing-Yun Li (International Journal of Biometeorology, 2017)

Preparation and Evaluation of Diosgenin Nanocrystals to Improve Oral Bioavailability - Cui-zhe Liu; Jin-hua Chang; Lin Zhang; He-fei Xue; Xi-gang Liu; Pei Liu; Qiang Fu (AAPS PharmSciTech, 2017)

Comprehensive functional analysis of Rab GTPases in Drosophila nephrocytes - Yulong Fu; Jun-yi Zhu; Fujian Zhang; Adam Richman; Zhanzheng Zhao; Zhe Han (Cell and Tissue Research, 2017)

Full-scale field load testing of long drilled shafts with enlarged base constructed in marine sediment - Kai-Fu Liu; Xin-Yu Xie; Zhe Luo; Qing-Hong Hu; Chun-Xia Huang (Marine Georesources & Geotechnology, 2017)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Cloning and Characterization of a Pyruvate Carboxylase Gene from Penicillium rubens and Overexpression of the Genein the Yeast Yarrowia lipolytica for Enhanced Citric Acid Production - Ge-Yi Fu; Yi Lu; Zhe Chi; Guang-Lei Liu; Shou-Feng Zhao; Hong Jiang; Zhen-Ming Chi (Marine Biotechnology, 2016)

Effects of heat stress on serum Cortisol, alkaline phosphatase activity and heat shock protein 40 and 90β mRNA expression in rainbow trout Oncorhynchus mykiss - Zhen Li; Zhe Liu; Yan Ni Wang; Yu Jun Kang; Jian Fu Wang; Hai Na Shi; Jin Qiang Huang; Li Jiang (Biologia, 2016)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Phylogenetic analysis of 32 porcine circovirus type 2 isolates from Shandong, China - Jianli Shi; Shaojian Xu; Fang Fu; Xiaoyan Cong; Xiaoyuan Yuan; Zhe Peng; Jiaqiang Wu; Wenbo Sun; Yijun Du; Jun Li; Baohua Huang; Jinbao Wang (Archives of Virology, 2015)

Isolation and characterization of 10 polymorphic microsatellite loci from the Chinese ratsnake (Zaocys dhumnades) - Rong-Fang Wang; Chao-Nan Zhu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Isolation and characterization of microsatellite loci in the Ussuri mamushi (Gloydius ussuriensis) - Rong-Fang Wang; Yan-Qing Wu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Bacterial diversity in saline-alkali ponds rearing common carp (Cyprinus carpio) as revealed by 16S rRNA gene sequences - Jin Qiang Huang; Zhe Liu; Yong Juan Li; Jian Fu Wang (Biologia, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

Non-Esterified Fatty Acids Activate the AMP-Activated Protein Kinase Signaling Pathway to Regulate Lipid Metabolism in Bovine Hepatocytes - Xinwei Li; Xiaobing Li; Hui Chen; Liancheng Lei; Juxiong Liu; Yuan Guan; Zhaoxi Liu; Liang Zhang; Wentao Yang; Chenxu Zhao; Shixin Fu; Peng Li; et al. (Cell Biochemistry and Biophysics, 2013)

The Effect of Deposition Se on the mRNA Expression Levels of GPxs in Goats from a Se-enriched County of China - Lei Zhang; Zhan-qin Zhou; Guang Li; Ming-zhe Fu (Biological Trace Element Research, 2013)

Polymorphisms in MHC class Ia genes and resistance to IHNV in rainbow trout (Oncorhynchus mykiss) - Zhe Liu; Dan Dan Hu; Shu Juan Shao; Juan Yang; Jian Fu Wang; Jin Qiang Huang (Genes & Genomics, 2013)

Analysis of main controlling factors for hydrocarbon accumulation in central rift zones of the Hailar-Tamtsag Basin using a fault-caprock dual control mode - XiaoFei Fu; Zhe Chen; BaiQuan Yan; Mian Yang; YongHe Sun (Science China Earth Sciences, 2013)

Celastrol exerts synergistic effects with PHA-665752 and inhibits tumor growth of c-Met-deficient hepatocellular carcinoma in vivo - Hong-Lei Jiang; Jun-Zhe Jin; Dan Wu; Dong Xu; Guo-Fu Lin; Hao Yu; Dong-Yan Ma; Jian Liang (Molecular Biology Reports, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Effect of ARHI on lung cancer cell proliferation, apoptosis and invasion in vitro - Xiaohong Wu; Li Liang; Liangliang Dong; Zhe Yu; Xiaoqing Fu (Molecular Biology Reports, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Laticiferous canal formation in fruits of Decaisnea fargesii: a programmed cell death process? - Ya-Fu Zhou; Wen-Zhe Liu (Protoplasma, 2011)

PTOV1 is associated with UCH-L1 and in response to estrogen stimuli during the mouse oocyte development - Yu-Wei Yao; Yan Shi; Zhe-Fu Jia; Ya-Hong Jiang; Zheng Gu; Jian Wang; Mohamad Aljofan; Zhao-Gui Sun (Histochemistry and Cell Biology, 2011)

Inhibition of hepatitis B virus replication by small interference RNA induces expression of MICA in HepG2.2.15 cells - Kai-Fu Tang; Min Chen; Jing Xie; Guan-Bin Song; Yi-Song Shi; Qi Liu; Zhe-Chuan Mei; Alexander Steinle; Hong Ren (Medical Microbiology and Immunology, 2009)

On the ability of the regional climate model RIEMS to simulate the present climate over Asia - Zhe Xiong; Congbin Fu; Qing Zhang (Advances in Atmospheric Sciences, 2006)

Analysis of simulated heavy rain over the Yangtze River valley during 11–30 June 1998 using RIEMS - Xiong Zhe; Wang Shuyu; Zeng Zhaomei; Fu Congbin (Advances in Atmospheric Sciences, 2003)

Streamflow simulation for the Yellow River basin using RIEMS and LRM - Jingyong Zhang; Wenjie Dong; Congbin Fu; Lingyun Wu; Zhe Xiong; Jun Ma; Kejia Zhang (Advances in Atmospheric Sciences, 2003)

Addenda - Xiao-feng Fu; Zhe Li (Journal of Geographical Sciences, 2001)

On coordinated development of oasis and environment in arid area - Fu Xiao-feng; Li Zhe (Journal of Geographical Sciences, 2001)